Constructing a Monolith: State Policy, Institutional DEI Plans, and the Flattening of Latinx Identity at Hispanic-Serving Institutions - Ishara Casellas Connors (SAGE Publishing, 2021)
As racialized institutions, Hispanic-serving institutions educate large portions of racially minoritized students within organizational and policy structures that advance Whiteness. This research considers how the institution-level diversity, equity, and inclusion (DEI) plans, produced in response to state-level DEI policies in Florida, California, and New York, construct narratives of intersectional diversity and a racialized Latinx identity at Hispanic-serving community colleges (HSCCs). Engaging critical discourse analysis, drawing together critical race theory and LatCrit, the analysis expands the consideration of DEI policy implementation at HSCCs. The findings illustrate the interconnectedness of state-level policy, policy implementation guidance, and institution-level discourse related to defining intersectional diversity and demographic data. Furthermore, it captures a lack of attention to racial composition among Latinx students and the limited characterization of HSI status. This study highlights how the implementation of state-level DEI policies can advance or erase the considerations of intersectionality among Latinx students.